40Ar–39Ar age constraint on deformation and brittle–ductile transition of the Main Central Thrust and the South Tibetan Detachment zone from Dhauliganga valley, Garhwal Himalaya, India. (August 2015) - Sen, Koushik; Chaudhury, Reetam; Pfänder, Jörg
Highlights: Timing of ductile–brittle transition in MCT and STD of Garhwal Himalaya constrained. Deformation in South Tibetan Detachment outlasted magmatism and pluton growth. The MCT wedge attained 'supercritical' stage due to rapid exhumation at ∼10 Ma. Erosion lowered taper angle of the MCT wedge, causing internal deformation. Transition from ductile to brittle deformation regime in the MCT occurred at ∼6 Ma. Abstract: 40 Ar– 39 Ar data from two sets of mylonitic two-mica granites present in the Main Central Thrust (MCT) and one leucogranite from the South Tibetan Detachment (STD) of Dhauliganga valley, Garhwal Himalaya are presented. The MCT and the STD bound the High Himalayan Crystallines (HHC) and are believed to facilitate its extrusion. Field evidence of ductile deformation in the form of tight isoclinal folding and brittle deformation in the form of back thrusts and transverse fractures are observed. The STD zone shows evidence of pervasive migration of leucogranitic melt through north dipping extensional shear zones. The ∼19.5 Ma old Malari Leucogranite, present adjacent to the STD zone, experienced ductile and brittle deformation related to the tectonics of the STD. Muscovite analysis from the Malari leucogranite gives a cooling age of ∼15.2 Ma suggesting that ductile deformation in the STD zone may have ceased by ∼15 Ma. 40 Ar– 39 Ar chronology of biotite from two mylonitic granites of the MCT yields cooling ages of 10.8 Ma and 9.7 Ma, which we correlate with activity of the MCT at ∼10 Ma that caused rapid exhumation of the HHC. 40 Ar– 39 Ar ages of 6.4 Ma and 6.2 Ma from white mica represent newly crystallized white mica post-dating biotite cooling and indicate late stage deformation. It is inferred that, as the HHC wedge started to exhume and erode rapidly along the MCT zone at ∼10 Ma, the taper angle of the Himalayan wedge decreased to a 'sub-critical' stage. To regain the critical taper angle, the wedge underwent internal deformation in the form of back thrusts and duplex structures. Comparison of our data with earlier results from other sections of the MCT helps us envisage that the ∼6 Ma white mica ages can be correlated with this internal deformation event and also with the transition of deformation regime in the MCT zone from ductile to brittle.